2016
DOI: 10.1080/03601234.2016.1191916
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of long duration high-volume sampling coupled to SPME-GC-MS/MS for the assessment of airborne pesticides variability in an urban area (Strasbourg, France) during agricultural application

Abstract: Atmospheric samples have been collected between 14 March and 12 September 2012 on a 2-week basis (15 days of sampling and exchange of traps each 7 days) in Strasbourg (east of France) for the analysis of 43 pesticides. Samples (particle and gas phases) were separately extracted using Accelerated Solvent Extraction (ASE) and pre-concentrated by Solid Phase Micro-Extraction (SPME) before analysis by gas chromatography coupled to tandem mass spectrometry (GC-MS/MS). Four SPME consecutive injections at distinct te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These pesticides are frequently detected in France and various countries (e.g. Bedos et al, 2010;Bedos et al, 2017;Degrendele et al, 2016;Désert et al, 2018;Follak et al, 2005;Houbraken et al, 2016;Liaud et al, 2016;Locke et al, 1996;Villiot et al, 2018;Whang et al, 1993), except dimethenamid-P and fenbuconazole for which no data could be found. The pesticides that were observed in the highest number of sites (four over five) were chlorothalonil (fungicide), dimethenamid-P and pendimethalin (two herbicides), while the highest concentrations were found for chlorpyrifos-methyl (insecticide; it has to be underlined that chlorpyrifos-methyl was recently banned in Europe in December 2019; EU -Pesticides database, 2020) followed by dimethenamid-P, pendimethalin, folpet (fungicide), S-metolachlor (herbicide) and chlorothalonil (Table 2; Fig.…”
Section: Pesticides Measured In the Airmentioning
confidence: 99%
“…These pesticides are frequently detected in France and various countries (e.g. Bedos et al, 2010;Bedos et al, 2017;Degrendele et al, 2016;Désert et al, 2018;Follak et al, 2005;Houbraken et al, 2016;Liaud et al, 2016;Locke et al, 1996;Villiot et al, 2018;Whang et al, 1993), except dimethenamid-P and fenbuconazole for which no data could be found. The pesticides that were observed in the highest number of sites (four over five) were chlorothalonil (fungicide), dimethenamid-P and pendimethalin (two herbicides), while the highest concentrations were found for chlorpyrifos-methyl (insecticide; it has to be underlined that chlorpyrifos-methyl was recently banned in Europe in December 2019; EU -Pesticides database, 2020) followed by dimethenamid-P, pendimethalin, folpet (fungicide), S-metolachlor (herbicide) and chlorothalonil (Table 2; Fig.…”
Section: Pesticides Measured In the Airmentioning
confidence: 99%
“…Anthropogenic activities, especially agriculture, release large amounts of pesticides daily into the soil, water and air (Ippolito et al, 2015;Liaud et al, 2016). Annually, approximately four million tons of pesticides are applied around the globe (Ippolito et al, 2015) and disseminated by drift, surface runoff, and drainage into the environment (Aparicio et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GC–mass spectrometry (GC–MS) combined with solid‐phase extraction has been used for the determination of a group of 39 semivolatile compounds related to wine quality (pesticide residues, phenolic off‐flavours, phenolic pollutants, and bioactive stilbenes) . Solid‐phase microextraction (SPME) has also been applied in the detection of pesticides and other atmospheric contaminants by GC . The combination of HS and SPME makes chromatographic detection technology more powerful.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with SERS, gas chromatography (GC) and liquid chromatography (LC) are traditional methods that have been widely applied in the detection of volatile compounds for many years . Moreover, GC combined with solid‐phase extraction technology in headspace (HS) mode has great potential in the investigation of volatile and semivolatile compounds, such as pesticides and aromatic compounds . For example, GC–mass spectrometry (GC–MS) combined with solid‐phase extraction has been used for the determination of a group of 39 semivolatile compounds related to wine quality (pesticide residues, phenolic off‐flavours, phenolic pollutants, and bioactive stilbenes) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation